Influence of the instillations of modern fluoroquinolones and their cytotoxic effects on the conjunctiva epithelium in patients with the syndrome of the dry eye (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Application of antibacterial preparations of the fluoroquinolones group of III — TV generations is recommended by the European and American communities of ophthalmosurgeons as the most effective way of prevention of the postoperative endophthalmitis. The influence of regular administration of antibacterial preparations on the anterior segment of the eye is not investigated sufficiently except for the risk of development of the secondary syndrome of the dry eye under the effect of preservatives of eye drops.Purpose. To study the influence of the antibacterial preparations of the fluoroquinolones group of TTTgeneration — 0.5 % levofloxacin (with preservative benzalconium chloride) and TV generation — 0.5 % moxifloxacin (withoutpreservative) on the conjunctiva epithelium in patients with manifestations of the syndrome of the dry eye.Results. The analysis of the data of impression — cytologic study of the conjunctiva allowed to reveal presence of dystrophic changes of the conjunctiva epithelium in 86.8 % of cases. Tn making Shirmer's test there was revealed the normal level of production of the tear fluid in 24.3 % of patients, 66.3 % of patients had decreased secretions, and in 9.4 % of-patients there was hypersecretion of the tear fluid. Results of the correlation analysis showed that standard diagnostic tests and data of clinical of examination of the anterior section of the eye are of specific character and cannot fully the degree of severity of the dystrophic changes of the conjunctiva epithelium. On repeated examination of the patients it is revealed that instillations of 0.5 % moxifloxacin lead to stabilization of the precorneal tear film, while instillations of 0.5 %) levofloxacin — to deterioration of stability of the precorneal tear film, especially in hyposecretion of the tears that is associated with presence of the pre-servative benzalconium chloride in the commercial solution of 0.5 % levofloxacin.
Keywords: conjunctiva; dystrophy; fluoroquinolones; preservative